Klinische Sportmedizin - Bohm P; Abdul-Khaliq H; Rentzsch A; Scharhag J; Meyer T (Dynamic Media Sales Verlag, 2015)
In the context of her check up for sports eligibility, an 11-year-old professional female gymnast reported a retrosternal pain during high intensity parts of the fitness training. The physical examination revealed a 2/6 systolic murmur in the second left intercostal space without radiation and a fixed splitting of the second heart sound. Resting ECG showed right heart overload with right axis deviation, incomplete right bundle branch block as well as terminal negative T-waves in V1-V3. Transthoracic echocardiography revealed a relevant atrial septal defect (ASD) of secundum type with a left to right shunt and consecutive right heart overload. This finding could be confirmed both angiographically and by means of transoesophageal echocardiography. Due to the size of the defect and the lack of sufficient caudal septal rim, transcatheter closure with implantation of an Amplatzer Septal Occluder could not be successfully performed. Thus, the indication was given for a surgical repair of the ASD which was performed with direct suture closure (primary closure). The postoperative course was uneventful. No signs of chest pain were noticedafterresumption of her usual training in the same intensity. Isolated chest pain during exercise is an unusual leading symptom in ASD patients and should always be clarified with cardiac imaging. Based on this case report, the important role of the resting ECG and echocardiography in the setting of preparticipation screening can be emphasized.KEY WORDS:Thoracic Pain, ASD, Echocardiography, Sports Eligibility